VITALITAS BAHASA USING BANYUWANGI BERHADAPAN DENGAN PERATURAN GUBERNUR JAWA TIMUR NOMOR 19 TAHUN 2014: KISAH PENYUDUTAN BAHASA USING BANYUWANGI - M. Oktavia Vidiyanti (Badan Pengembangan dan Pembinaan Bahasa, 2016)
This paper is motivated by the Regulation of the Governor of East Java Number 19 of 2014 about the subject of local language as a local content that is required to be taught in elementary schools/madrasah, Madura and Javanese language. In the regulation, Using language is not included as one of the local contents. Meanwhile, the Local Regulation of Banyuwangi stated that Using language should be thought in elementary schools and junior high schools since 2007. It certainly caused paradox between the Regulation of the Governor and the Local Regulation of Banyuwangi Regency. This paper highlights how Using Bayuwangi language has high language vitality and is able to accommodate with other languages (i.e. Gintangan Village, Rogojampi District, Banyuwangi). The ability of Using language to survive within the society obviously draws questions as to why the Regulation of the Governor is unable to observe from the ethics and emic point of views. The ethics point of view mostly theoretically, which is probably temporary and needed to be verified, while the emic point of view tends to be practical, historical and concrete. A compromised solution may needed to be sought, for example only languages that are truly maintained by its people and proved to have high ethnolinguistic vitality that should be preserved, while others probably should be sacrificed. ABSTRAKMakalah ini bertolak pada Peraturan Gubernur Jawa Timur Nomor 19 tahun 2014 tentang mata pelajaran bahasa daerah sebagai muatan lokal wajib diajarkan sekolah/madrasah yaitu bahasa daerah Madura dan bahasa Jawa. Di dalam Peraturan Gubernur Jawa Timur tersebut Bahasa Using tidak diikutsertakan dalama muatan lokal tersebut. Sementara itu, Peraturan Daerah Banyuwangi yang memberlakukan bahasa daerah Using diajarkan di SD dan SMP sejak tahun 2007. Hal ini tentunya timbul paradoks di dalam Peraturan Gubernur dan Peraturan Daerah Kabupaten Banyuwangi. Tulisan ini menyoroti bagaimana bahasa Using Banyuwangi memiliki vitalitas bahasa yang tinggi dan mampu berakomodasi dengan bahasa di luar bahasa Using (sampel Desa Gintangan, Kecamatan Rogojampi, Banyuwangi). Kemampuan bahasa Using yang dapat bertahan di masyarakatnya tersebut tentunya memunculkan pertanyaan mengapa Peraturan Gubernur tidak melihat dari sudut pandangan etik dan emik dalam bahasa. Pandangan etik lebih banyak bersifat teoretis, masih bersifat sementara dan perlu diuji kebenarannya. Sementara pandangan emik lebih bersifat praktis, kesejarahan, dan kenyataan yang konkret. Untuk itu perlu dicari penyelesaian kompromistis, hanya bahasa yang benar-benar dipelihara oleh masyarakatnya, yang terbukti vitalitas etnolinguisnya tinggi, dan yang perlu dilestarikan.